Three-Dimensional Poroelastic Modeling of Multiple Hydraulic Fracture Propagation from Horizontal Wells. (May 2018) - Kumar, Dharmendra; Ghassemi, Ahmad
Abstract: Numerical simulations of multistage hydraulic fracturing usually neglect poroelastic effects. However, in case of low permeability reservoirs, where hydraulic fracturing is usually carried-out using relatively low viscosity fluids and high injection rates, coupled poroelastic mechanisms need be included for better understanding of the fracturing process, which can involve rock failure and/or reactivation of natural fractures. In this paper, we present a fully coupled three-dimensional poroelastic analysis of multiple fracture propagation from horizontal wells. The numerical model uses the indirect boundary element method of displacement discontinuity for poroelastic response of the rock, the finite element method for fracture fluid flow, and the linear elastic fracture mechanics approach for fracture propagation. The model accounts for the mechanical interactions among multiple fractures, mixed-mode propagation, fluid diffusion into the reservoir matrix, and the effects of fluid diffusion on the rock mechanical response. The model is verified with analytical solutions, and numerical examples of simultaneous and sequential fracturing of single and multiple horizontal wells in the Niobrara Chalk formation are presented. The results show the created fracture network geometries are strongly influenced by the mechanical interactions among the fractures. It is also demonstrated that the poroelastic effect increases the net fracture pressure and causes a reduction in fracture volume. The poroelastic model illustrates the transient character of stress shadow, and is particularly useful for re-fracturing analysis since it readily calculates the stress variations due to reservoir depletion. Highlights: A fully coupled three-dimensional poroelastic hydraulic fracture model is developed. The model uses the 3D displacement discontinuity method, and linear elastic fracture mechanics. The model simulates simultaneous or sequential multiple fractures and refracturing of horizontal wells. Simulation results illustrate that mechanical interaction is a critical design parameter for horizontal well fracturing. The fluid diffusion into reservoir rocks impacts the stress shadowing among multiple fractures.